The Net Is Not Neutral: Teaching Hidden Biases in Everyday Internet Use - Archer, Alyssa; Dinkle, Lisa; Bellamy, Liz (Université d'Ottawa | University of Ottawa, 2018)
From Facebook’s filter bubble to Google’s inappropriate autocorrects, proprietary algorithms distort information and reinforce biases. Engage in active learning exercises from a successful workshop series that demonstrate to our learners the non-neutrality of the web, and discuss ways to incorporate digital literacy into your praxis. Bring your mobile device/laptop!